Adaptive HR: impactful HR for the new and virtual world of work - Roux, Marianne (Knowledge Resources, 2021)
""In the new world of work, HR must be strategic driver of organisational agility and capability.""_x000D__x000D_Developed more than 20 years ago, current HR models are no longer relevant in the new world of work. If HR is going to provide the value and impact needed right now, a holistic reframing of the function, its purpose, capabilities, delivery and impact is needed! _x000D__x000D_Adaptive HR: Impactful HR for the New and Virtual World of Work is a complete guidebook to help HR professionals accelerate this transformation within their own organisations. _x000D__x000D_Adaptive HR: Impactfu.